Correlation of muscle BOLD MRI with transcutaneous oxygen pressure for assessing microcirculation in patients with systemic sclerosis. Issue 4 (25th February 2013) - Partovi, Sasan; Aschwanden, Markus; Jacobi, Bjoern; Schulte, Anja‐Carina; Walker, Ulrich A.; Staub, Daniel; Imfeld, Stephan; Broz, Pavel; Benz, Daniela; Zipp, Lisa; Jaeger, Kurt A.; Takes, Martin; et al.
Abstract : Purpose: To prospectively compare calf muscle BOLD MRI with transcutaneous oxygen pressure (TcPO2 ) measurement in patients with systemic sclerosis (SSc) and healthy volunteers and thereby get insight into the pathogenesis of vasculopathy in this connective tissue disorder. Materials and Methods: Twelve patients with SSc (6 women and 6 men, mean age 53.5 ± 10.0 years) and 12 healthy volunteers (4 men and 8 women, mean age 47 ± 12.1 years) were examined using muscle BOLD MRI and TcPO2 . A cuff compression at mid‐thigh level was performed to provoke ischemia and reactive hyperemia. BOLD measurements were acquired on a 3 Tesla whole body‐scanner in the upper calf region using a multi‐echo EPI‐sequence with four echo‐times (TE: 9/20/31/42 ms) and a repetition time of 2 s. Empirical cross‐correlation analysis depending on time lags between BOLD‐ and TcPO2 ‐measurements was performed. Results: Maximal cross‐correlation of BOLD T2*‐ and TcPO2 ‐measurements was calculated as 0.93 (healthy volunteers) and 0.90 (SSc patients) for a time lag of approximately 40 s. Both modalities showed substantial differences regarding time course parameters between the SSc patients and healthy volunteers. Conclusion: Skeletal muscle BOLD MRI correlated very well with TcPO2 . T2* changes seem to reflect reoxygenation deficits in deeper muscle tissue of SSc patients. J. Magn. Reson. Imaging 2013;38:845–851. © 2013 Wiley Periodicals, Inc.